Muscular contraction mode differently affects autonomic control during heart rate matched exercise - Weippert, Matthias; Behrens, Martin; Gonschorek, Ray; Bruhn, Sven; Behrens, Kristin (Frontiers in Physiology, 2015)
The precise contributions of afferent feedback to cardiovascular and respiratory responses to exercise are still unclear. Aim of this crossover study was to assess whether and how autonomic cardiovascular and respiratory control differed in response to dynamic (DYN) and isometric contractions (ISO) at a similar, low heart rate (HR) level. Therefore, 22 healthy males (26.7 ± 3.6 yrs) performed two kinds of voluntary exercises at similar HR: ISO and DYN of the right quadriceps femoris muscle. Although HR was eqivalent (82 ± 8 bpm for DYN and ISO, respectively), rating of exertion, blood pressures, and rate pressure product were higher, whereas breathing frequency, minute ventilation, oxygen uptake and carbon dioxide output were significantly lower during ISO. Tidal volume, end-tidal partial pressures of O2 and CO2, respiratory exchange ratio and capillary blood lactate concentration were comparable between both contraction modes. Heart rate variability (HRV) indicators, SDNN, HF-Power and LF-Power, representing both vagal and sympathetic influences, were significantly higher during ISO. Sample entropy, a nonlinear measure of HRV was also significantly affected by contraction mode. It can be concluded that, despite the same net effect on HR, the quality of cardiovascular control during low intensity exercise is significantly different between DYN and ISO. HRV analysis indicated a sympatho-vagal coactivation during ISO. Whether mechanoreceptor feedback alone, a change in central command, or the interaction of both mechanisms is the main contributor of the distinct autonomic responses to the different exercise modes remains to be elucidated.